Revisiting brainstorming within an educational context: A meta-thematic analysis - Doğan, Yunus; Batdı, Veli (Commonwealth of Learning, 2021)
An increase in research on the teaching of creativity in learning environments is being witnessed as more studies continue to reveal its effects on learning outcomes and academic achievement. Thus, any investigative attempt to examine the relevant approaches to teaching of creative thinking skills is appreciated within the creativity literature. However, it is evident that the research on brainstorming as a creativity-promoting technique within an educational context has been overlooked for a while. Therefore, this research synthesis tried to recombine and reinterpret the results of some qualitative studies on the impacts of brainstorming technique on learners’ achievement. To this end, 34 studies within the relevant literature were scanned; however, seven of them were found to be conducive to the meta-thematic analysis. The results of the meta-thematic analysis suggest that the brainstorming technique has positive effects on learners’ cognitive skills and affect. It is believed that designing instruction with brainstorming could foster students’ creativity by directing them to solving problems via critical thinking. The study further dwells on the reported drawbacks that are encountered during the implementation of this technique within the classroom and discusses some possible solutions as implications. © 2021, Commonwealth of Learning. All rights reserved.
Keywords: Academic achievement; Brainstorming; Creativity; Meta-thematic analysis; Thinking skills